Growth performance and sexual maturity in Malaysian Kedah-Kelantan and Kedah-Kelantan x Brangus bulls - Islam, Mohammed Sirajul; Yimer, Nurhusien; Haron, Wahid; Abdullah, Faez Firdaus Jesse; Hiew, Mark Wen Han; Kamalludin, Mamat Hamidi; Wan Nor Fitri; Kaka, Ubedullah; Quddus, Abdul (Nexus Academic Publishers, 2022)
Domestic beef production in Malaysia is mainly contributed by the indigenous Kedah-Kelantan (KK) and their crossbred cattle. This study was conducted to compare growth performance and sexual maturity of KK and KK × Brangus bulls. Ten (10) experimental bulls with similar ages were kept under the same paddock and fed with equal quality and quantity Guinea grasses and palm kernel cakes. Body weight was measured at monthly basis by using a digital animal weighing scale. Age at sexual maturity was determined by the time of semen ejaculation and quality. The results revealed significantly (p<0.05) greater body weight in KK × Brangus bulls (230.50±9.3 kg) as compared to the pure-bred KK bulls (204.5 ±13.2 kg) at 24 months of ages. KK bulls attained sexual maturity at an earlier age of 21.5±0.4 months, while KK × Brangus bulls attained at 28.8±0.5 months. The growth performance of KK × Brangus bulls was significantly (p˂0.05) higher than KK bulls. Age showed a significant positive correlation with body weight and average daily weight gains. In conclusion, KK pure-bred bulls were superior in terms of attaining age at puberty and sexual maturity earlier, whereas KK × Brangus bulls were better for growth performance.